2002
DOI: 10.1080/003655202761020551
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Human Tissue Transglutaminase: Superior Predictors of Coeliac Disease

Abstract: All human antigen kits showed significantly higher sensitivity for coeliac disease compared to guinea pig antigen (P < 0.001). Receiver operating characteristic curves confirmed the superior diagnostic accuracy of the human antigen kits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The prevalence of CD exhibits an iceberg effect; the number of asymptomatic cases with positive serology and biopsy is 5-to 7-fold higher than typical symptomatic individuals exhibiting signs and symptoms including abdominal pain, growth retardation, short stature, chronic diarrhea, iron deficiency anemia that is refractive to treatment and intestinal lymphoma (6,12,21,29) . Serologic tests such as the anti-endomysium IgA antibody test (EMA), the anti-tissue transglutaminase immunoglobulin (Ig) A antibody test (anti-tTG Ab) and HLA DQ2 or DQ8 genotype testing are useful for evaluation of asymptomatic subjects as well as patients with diabetes mellitus, thyroiditis, Down syndrome, Turner syndrome, William syndrome, IgA deficiency and first-degree relatives of patients with CD (1,4,5,17) . It is therefore logical to screen these populations for other autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of CD exhibits an iceberg effect; the number of asymptomatic cases with positive serology and biopsy is 5-to 7-fold higher than typical symptomatic individuals exhibiting signs and symptoms including abdominal pain, growth retardation, short stature, chronic diarrhea, iron deficiency anemia that is refractive to treatment and intestinal lymphoma (6,12,21,29) . Serologic tests such as the anti-endomysium IgA antibody test (EMA), the anti-tissue transglutaminase immunoglobulin (Ig) A antibody test (anti-tTG Ab) and HLA DQ2 or DQ8 genotype testing are useful for evaluation of asymptomatic subjects as well as patients with diabetes mellitus, thyroiditis, Down syndrome, Turner syndrome, William syndrome, IgA deficiency and first-degree relatives of patients with CD (1,4,5,17) . It is therefore logical to screen these populations for other autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…for the detection of anti-tTG antibodies (10,13,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Few studies, however, have compared the available htTG-based tests (10,17,(25)(26)(27), and these studied only a limited number of the available tests [three methods in Ref.…”
mentioning
confidence: 99%
“…Few studies, however, have compared the available htTG-based tests (10,17,(25)(26)(27), and these studied only a limited number of the available tests [three methods in Ref. (27 ), four in Refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second-generation kits using purified human tTG or human recombinant tTG were developed and introduced in routine practice. Several studies compared the firstand second-generation kits and concluded that the human antigens improve assay sensitiv-ity and selectivity [63,[74][75][76]. A third generation of kits using tTG-gliadin peptide complexes as the antigen has also been proposed; however, it seems to have no advantage over human recombinant antigen kits, especially regarding specificity [77,78].…”
Section: Biological Markersmentioning
confidence: 99%